La violencia sexual contra la mujer : legalización de los sistemas de protección - Rein, Tatiana (Estudios Internacionales, 2005)
Starting from the premise that the protection granted to women against sexual violence may vary according to the timing of the attack, the international systems for the protection of human rights specifically applicable to the matter are examined, with special reference to the system of the United Nations and the Inter-American System that are effective in periods of peace, as well as the system that is applied in times of armed conflict, focusing on the International Criminal Court and the relevant Statute. The study is based on the theory of legalization, as set out in the work Legalization and World Politics, which establishes the requirements that institutions must meet to determine their degree of development.